Quality of Life with Late-Onset Pompe Disease: Qualitative Interviews and General Public Utility Estimation in the United Kingdom - Lena Hubig; Anna-Katrine Sussex; Alasdair MacCulloch; Derralynn Hughes; Ryan Graham; Liz Morris; Syed Raza; Andrew J. Lloyd; Amanda Sowinski; Katy Gallop (Journal of Health Economics and Outcomes Research, 2023)
# Background Late-onset Pompe disease (LOPD) is a rare, progressive neuromuscular condition typically characterized by weakness of skeletal muscles, including those involved in respiration and diaphragmatic dysfunction. Individuals with LOPD typically eventually require mobility and/or ventilatory support.